Characterizing Interoperability in Context-Aware Software Systems - Motta, Rebeca Campos; Oliveira, Káthia Marçal de; Travassos, Guilherme Horta (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2016: Anais do VI Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2016)
Context-awareness feature has been widely employed in the last years due to their usefulness to enhance systems functional reliability and user experience. Different software and hardware technologies can be integrated and used to capture context information, without user intervention. However, the heterogeneity of technology makes interoperability a great development challenge. Moreover, its evaluation for the context-aware system is also not trivial. Considering the relevance of the topic, we performed a characterization research (secondary study) aiming at revealing evidence on how interoperability has been addressed in context-aware software systems (CASS). Despite the observed conceptual divergence on interoperability, we present a set of evidence-based characteristics that can support decision-making and evaluation of interoperability on such systems. This work also introduces some research challenges aiming at to improve what we know about interoperability in CASS.